LINGUISTIC CHARACTERISTICS OF ANTHROPOMORPHS IN THE LANGUAGE OF OGAHIY'S HISTORICAL WORKS - Karimova Shahlo Abdullayevna (Journals Park Publishing, 2023)
This article analyzes anthropomorphs in Ogahiy's works and explains their linguistic characteristics based on examples.
Keywords: anthropomorphology, artistic text, linguistic unity, allyuziv name, pretsedent units.